Low-temperature-resistant anti-freezing thermal insulation rubber and plastic and preparation process thereof
By using specific combinations of raw materials and processes, low-temperature and freezing insulation rubber and plastics with excellent mechanical, flame retardant and low-temperature resistance are prepared, which solves the problem of insufficient performance of existing products and has a broader market prospect.
Patent Information
- Application Number
- CN202510412834.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing low-temperature and freezing insulation rubber and plastics have insufficient flame retardant and low-temperature resistance and need further improvement.
The raw materials such as methyl vinyl silicone rubber, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butyl peroxide) hexane, tetramethyl divinyl disiloxane, chloroplatinic acid hexahydrate, silicon-containing polyurethane and antioxidants were used to mix and cleavage and extrude and granulate, and press-formed in a flat vulcanizer to prepare low-temperature, freezing and heat-resistant rubber and plastic.
It has achieved good mechanical properties, excellent flame retardant properties and excellent low temperature resistance and freezing insulation properties, effectively ensuring the quality and quality of the product.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to low temperature resistant, antifreeze and heat-insulating rubber and plastic and a preparation process thereof. Background Art
[0002] Rubber and plastic is a general term for the rubber and plastic industries. They are all by-products of petroleum. They have the same source, but in the process of making products, their physical properties are different and their uses are even more different. Rubber is widely used in industries such as tires, and plastics are becoming more and more widely used with the demand of technology and market.
[0003] In the patent document with application number "CN202310907926.8" and titled "A low-temperature resistant rubber-plastic insulation material prepared from natural rubber", it is recorded that "it includes the following raw materials in parts by weight: 9-13 parts of natural rubber, 12-16 parts of skeleton resin, 1.8-3 parts of reinforcing resin, 0.1-0.3 parts of curing agent, 10-15 parts of foaming agent, 23-28 parts of aluminum hydroxide, 18-23 parts of chlorinated paraffin oil, 1-3 parts of epoxidized soybean oil, 1-3 parts of solid paraffin, 2 parts of pigment carbon black ~3.5 parts, antimony trioxide 0.5~1 parts, polyethylene glycol 1~2 parts, stearic acid 0.2-0.5 parts, sulfur 0.1~0.5 parts, vulcanization accelerator 1~1.5 parts, activator 0.1~0.5 parts, heat stabilizer 0.1~0.4 parts, antioxidant 0.8~1.5 parts, anti-scorch agent 0.05~0.1 parts; the present invention realizes the blending of natural rubber with polyvinyl chloride and chlorinated polyethylene, and the obtained rubber-plastic thermal insulation material has good low temperature resistance, high hardness, high elasticity, and good application prospects.
[0004] Although the thermal insulation rubber and plastic manufactured by the above patent documents have certain thermal insulation properties, their flame retardancy and low temperature resistance are relatively insufficient and still need further improvement. Based on this, the present invention provides low temperature resistant and antifreeze thermal insulation rubber and plastic and its preparation process to solve the above technical problems. Summary of the invention
[0005] The purpose of the present invention is to provide low-temperature resistant, antifreeze and thermal insulation rubber and plastic and its preparation process. The low-temperature resistant, antifreeze and thermal insulation rubber and plastic prepared by the present invention not only has good mechanical properties, but also has excellent flame retardant properties. At the same time, it also has excellent low-temperature resistant, antifreeze and thermal insulation properties, effectively ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a low-temperature resistant, antifreeze and thermal insulation rubber and plastic, which is composed of the following raw materials in parts by weight: 20 to 30 parts of methyl vinyl silicone rubber, 10 to 20 parts of polyether polyurethane, 3 to 5 parts of composite fillers, 2 to 4 parts of flame retardants, 4 to 7 parts of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, 6 to 10 parts of tetramethyldivinyldisiloxane, 4 to 6 parts of hexahydrated chloroplatinic acid, 2 to 3 parts of silicon-containing polyurethane and 2 to 5 parts of antioxidants.
[0007] Furthermore, the preparation process of the composite filler is as follows: The microporous calcium silicate is heated to 70-80° C., then placed in a stirring device, and γ-aminopropyltriethoxysilane is added into the stirring device, mixed for 10-15 minutes at 70-80° C. and 120-140 r / min, and after being discharged, placed in a drying oven at 80-90° C. and dried to constant weight to obtain modified microporous calcium silicate; The obtained modified microporous calcium silicate was ultrasonically differentiated for 200 to 220 minutes to obtain modified microporous calcium silicate powder, and an appropriate amount of the modified microporous calcium silicate powder was placed in deionized water at a dosage ratio of 0.02 to 0.12 g / mL, and after ultrasonic dispersion for 20 to 30 minutes, 2% to 12% of the modified carbon fiber by weight of the modified microporous calcium silicate powder was added thereto, and the mixture was treated at 60 to 70° C. for 120 to 160 minutes, and after suction filtration, the mixture was placed in a drying oven at 80 to 90° C. and dried to constant weight to obtain a composite material; An appropriate amount of the composite material is placed in deionized water at a dosage ratio of 0.22-0.32 g / mL, and after ultrasonic dispersion for 20-30 minutes, 2.2%-2.4% of methyl methacrylate and 0.11%-0.22% of potassium persulfate by weight of the composite material are added thereto respectively, and reflux treatment is carried out for 180-200 minutes under water bath conditions of 120-220 r / min and 75-80° C., and after suction filtration, the mixture is washed with deionized water for 2-5 times, and then dried in a drying oven at 80-90° C. to constant weight to obtain a thermal insulation filler.
[0008] Furthermore, the added amount of the γ-aminopropyltriethoxysilane is 6.2% to 8.2% of the mass of the microporous calcium silicate.
[0009] Furthermore, the preparation process of the modified carbon fiber is as follows: Place an appropriate amount of carbon fiber in the modifier at a dosage ratio of 0.04-0.14 g / mL, and perform ultrasonic treatment for 60-70 min. After the ultrasonic treatment, heat the mixture to 50-70°C, and perform reflux treatment for 100-120 min at 80-100 r / min. The filter cake is then filtered and washed 2 to 4 times with deionized water, and then placed in a drying oven at 50 to 70° C. and dried to a constant temperature to obtain modified carbon fibers.
[0010] Furthermore, the modifier is selected from any one of 65% to 70% concentrated sulfuric acid and 68% to 80% concentrated nitric acid.
[0011] Furthermore, the preparation process of the flame retardant is as follows: Place an appropriate amount of magnesium hydroxide in deionized water at a dosage ratio of 0.08 to 0.12 g / mL and ultrasonically disperse for 20 to 30 minutes to obtain a suspension; Add 0.12% to 0.23% by mass of magnesium hydroxide modified hollow glass microspheres to the obtained suspension, treat at 70 to 78°C and 120 to 240 r / min for 300 to 320 min, filter, wash with deionizer 2 to 4 times, and then dry in a drying oven at 80 to 90°C to constant weight to obtain a flame retardant.
[0012] Furthermore, the preparation process of the modified hollow glass microspheres is as follows: A suitable amount of γ-glycidyloxypropyltrimethoxysilane is placed in anhydrous ethanol at a mass ratio of 0.12 to 0.22:1 and mixed thoroughly, and then the pH value is adjusted to 4.2 to 5.2 with hydrochloric acid to obtain a composite solution; An appropriate amount of hollow glass microspheres is placed in the composite solution at a dosage ratio of 0.23 to 0.33 g / mL, treated at 30 to 40 r / min for 150 to 170 minutes, filtered, and then placed in a drying oven at 40 to 50° C. to dry to constant weight to obtain modified hollow glass microspheres.
[0013] Furthermore, the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
[0014] The second aspect of the present invention: also provides a preparation process of the above-mentioned low temperature resistant, antifreeze and heat-insulating rubber and plastic, comprising the following steps: Step 1, accurately weighing methyl vinyl silicone rubber, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tetramethyldivinyldisiloxane, hexahydrated chloroplatinic acid, silicon-containing polyurethane and antioxidant, and putting the raw materials into a mixing device for mixing and stirring, and then mixing and extruding to obtain pellets; Step 2: Move the pellets to a flat vulcanizer for pressure molding, and the final product is a low-temperature resistant, antifreeze and thermal insulation rubber and plastic product.
[0015] Furthermore, in the step 2, the pressure of the pressurization is 6-8 MPa, the temperature is 155-165° C., and the vulcanization time is set to 40-60 min.
[0016] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, methyl vinyl silicone rubber, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butyl peroxide) hexane, tetramethyl divinyl disiloxane, hexahydrated chloroplatinic acid, silicon-containing polyurethane and antioxidant are used as raw materials, and methyl vinyl silicone rubber, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butyl peroxide) hexane, tetramethyl divinyl disiloxane, hexahydrated chloroplatinic acid, silicon-containing polyurethane and antioxidant are mixed, kneaded and extruded to granulate to obtain pellets, and then the pellets are moved to a flat vulcanizer for pressure molding, and the final product is a low-temperature resistant, antifreeze and heat-insulating rubber and plastic product. The low-temperature resistant, antifreeze and heat-insulating rubber and plastic prepared by the present invention not only has good mechanical properties, but also has excellent flame retardant properties, and at the same time, it also has excellent low-temperature resistant, antifreeze and heat-insulating properties, which effectively guarantees its quality. The low-temperature resistant, antifreeze and heat-insulating rubber and plastic and the preparation process thereof provided by the present invention have broader market prospects and are more suitable for promotion. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1: This example provides a low-temperature resistant, antifreeze and thermal insulation rubber and plastic, which is composed of the following raw materials in parts by weight: 20 parts of methyl vinyl silicone rubber, 10 parts of polyether polyurethane, 3 parts of composite fillers, 2 parts of flame retardants, 4 parts of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, 6 parts of tetramethyldivinyldisiloxane, 4 parts of hexahydrated chloroplatinic acid, 2 parts of silicon-containing polyurethane and 2 parts of antioxidants.
[0019] In this embodiment, it should be noted that the methyl vinyl silicone rubber was purchased from Guangzhou Shisheng Chemical Co., Ltd., the polyether polyurethane was purchased from Shanghai Fengguang Plastic Technology Co., Ltd., and the silicon-based polyurethane TPU was purchased from Meirui New Materials Company.
[0020] The preparation process of the composite filler is as follows: The microporous calcium silicate is heated to 70° C., then placed in a stirring device, and γ-aminopropyltriethoxysilane is added into the stirring device, mixed for 10 minutes at 70° C. and 120 r / min, and after being discharged, placed in a drying oven at 80° C. and dried to constant weight to obtain modified microporous calcium silicate; The obtained modified microporous calcium silicate was ultrasonically differentiated for 200 minutes to obtain modified microporous calcium silicate powder, and an appropriate amount of the modified microporous calcium silicate powder was placed in deionized water at a dosage ratio of 0.02 g / mL, and after ultrasonic dispersion for 20 minutes, 2% of the modified carbon fiber by weight of the modified microporous calcium silicate powder was added thereto, and the mixture was treated at 60° C. for 120 minutes, and after suction filtration, the mixture was placed in a drying oven at 80° C. and dried to constant weight to obtain a composite material; An appropriate amount of the composite material was placed in deionized water at a dosage ratio of 0.22 g / mL. After ultrasonic dispersion for 20 minutes, 2.2% of methyl methacrylate and 0.11% of potassium persulfate by weight of the composite material were added thereto respectively. The mixture was refluxed for 180 minutes in a water bath at 120 r / min and 75°C. After filtration, the mixture was washed twice with deionized water and dried in a drying oven at 80°C to constant weight to obtain a thermal insulation filler.
[0021] Furthermore, the added amount of γ-aminopropyltriethoxysilane is 6.2% of the mass of the microporous calcium silicate.
[0022] The preparation process of modified carbon fiber is as follows: An appropriate amount of carbon fiber was placed in the modifier at a dosage ratio of 0.04 g / mL, and ultrasonic treatment was performed for 60 min. After the ultrasonic treatment was completed, the temperature was raised to 50°C and refluxed at 80 r / min for 100 min. The filter cake was then filtered and washed twice with deionized water, and then placed in a drying oven at 50° C. and dried to a constant temperature to obtain modified carbon fibers.
[0023] Among them, the modifier is concentrated sulfuric acid with a concentration of 65%.
[0024] In this embodiment, it should be noted that microporous calcium silicate was purchased from Qinghe County Ruijiang Metal Materials Co., Ltd., and carbon fiber was purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.
[0025] In addition, the preparation process of the flame retardant is as follows: An appropriate amount of magnesium hydroxide was placed in deionized water at a dosage ratio of 0.08 g / mL and ultrasonically dispersed for 20 min to obtain a suspension; To the obtained suspension, 0.12% of the mass of magnesium hydroxide modified hollow glass microspheres were added, and the suspension was treated at 70°C and 120 r / min for 300 min. After filtration, the suspension was washed twice with deionized water, and then dried in a drying oven at 80°C to constant weight to obtain a flame retardant.
[0026] Further, the preparation process of the modified hollow glass microspheres is as follows: An appropriate amount of γ-glycidyloxypropyltrimethoxysilane was placed in anhydrous ethanol at a mass ratio of 0.12:1 and mixed thoroughly, and then the pH value was adjusted to 4.2 with hydrochloric acid to obtain a composite solution; An appropriate amount of hollow glass microspheres was placed in the composite solution at a dosage ratio of 0.23 g / mL, treated at 30 r / min for 150 min, filtered, and then placed in a drying oven at 40° C. to dry to constant weight to obtain modified hollow glass microspheres.
[0027] In this embodiment, it should be noted that the hollow glass microspheres were purchased from Shanghai Kaishengli Chemical Co., Ltd.
[0028] Among them, antioxidant 1010 is selected as the antioxidant.
[0029] In addition, this embodiment also provides a preparation process of the above-mentioned low temperature resistant, antifreeze and heat-insulating rubber and plastic, comprising the following steps: Step 1: Accurately weigh methyl vinyl silicone rubber, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tetramethyldivinyldisiloxane, hexahydrated chloroplatinic acid, silicon-containing polyurethane and antioxidant, and put the raw materials into a mixing equipment for mixing and stirring, and then perform internal mixing, extrusion and granulation to obtain granules.
[0030] Step 2: Move the pellets to a flat vulcanizer for pressure molding, and the final product is a low-temperature resistant, antifreeze and thermal insulation rubber and plastic product.
[0031] The pressure of the press molding was 6 MPa, the temperature was 155°C, and the vulcanization time was set to 40 min.
[0032] Example 2: The preparation process of the low temperature resistant, antifreeze and heat-insulating rubber and plastic provided in this example is basically the same as that in Example 1, except that: the specific raw material composition and specific preparation process of the low temperature resistant, antifreeze and heat-insulating rubber and plastic in this example are different; the specific raw material composition and specific preparation process of the low temperature resistant, antifreeze and heat-insulating rubber and plastic in this example are as follows: A low-temperature resistant, antifreeze and heat-insulating rubber-plastic is composed of the following raw materials in parts by weight: 25 parts of methyl vinyl silicone rubber, 15 parts of polyether polyurethane, 4 parts of composite fillers, 3 parts of flame retardants, 5 parts of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, 8 parts of tetramethyldivinyldisiloxane, 5 parts of hexahydrated chloroplatinic acid, 3 parts of silicon-containing polyurethane and 3 parts of antioxidants.
[0033] In this embodiment, it should be noted that the methyl vinyl silicone rubber was purchased from Guangzhou Shisheng Chemical Co., Ltd., the polyether polyurethane was purchased from Shanghai Fengguang Plastic Technology Co., Ltd., and the silicon-based polyurethane TPU was purchased from Meirui New Materials Company.
[0034] The preparation process of the composite filler is as follows: The microporous calcium silicate is heated to 75° C., then placed in a stirring device, and γ-aminopropyltriethoxysilane is added into the stirring device, mixed for 12 minutes at 75° C. and 130 r / min, and after being discharged, placed in a drying oven at 85° C. and dried to constant weight to obtain modified microporous calcium silicate; The obtained modified microporous calcium silicate was ultrasonically differentiated for 210 minutes to obtain modified microporous calcium silicate powder, and an appropriate amount of the modified microporous calcium silicate powder was placed in deionized water at a dosage ratio of 0.07 g / mL. After ultrasonic dispersion for 25 minutes, 8% of the modified carbon fiber by weight of the modified microporous calcium silicate powder was added thereto, and the mixture was treated at 65° C. for 140 minutes. After suction filtration, the mixture was placed in a drying oven at 85° C. and dried to constant weight to obtain a composite material; An appropriate amount of the composite material was placed in deionized water at a dosage ratio of 0.27 g / mL. After ultrasonic dispersion for 25 minutes, 2.3% of methyl methacrylate and 0.16% of potassium persulfate by weight of the composite material were added thereto respectively. The mixture was refluxed for 190 minutes in a water bath at 170 r / min and 78°C. After filtration, the mixture was washed three times with deionized water and dried in a drying oven at 85°C to constant weight to obtain a thermal insulation filler.
[0035] Furthermore, the added amount of γ-aminopropyltriethoxysilane is 7.2% of the mass of the microporous calcium silicate.
[0036] The preparation process of modified carbon fiber is as follows: An appropriate amount of carbon fiber was placed in the modifier at a dosage ratio of 0.09 g / mL, and ultrasonic treatment was performed for 65 min. After the ultrasonic treatment was completed, the temperature was raised to 60°C and refluxed at 90 r / min for 110 min. The filter cake was then filtered and washed three times with deionized water, and then placed in a drying oven at 60° C. and dried to a constant temperature to obtain modified carbon fibers.
[0037] Among them, the modifier is concentrated sulfuric acid with a concentration of 70%.
[0038] In this embodiment, it should be noted that microporous calcium silicate was purchased from Qinghe County Ruijiang Metal Materials Co., Ltd., and carbon fiber was purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.
[0039] In addition, the preparation process of the flame retardant is as follows: An appropriate amount of magnesium hydroxide was placed in deionized water at a dosage ratio of 0.1 g / mL and ultrasonically dispersed for 25 min to obtain a suspension; To the obtained suspension, 0.17% of magnesium hydroxide by mass of modified hollow glass microspheres was added, and the suspension was treated at 74°C and 180 r / min for 310 min. After filtration, the suspension was washed with deionized water for 3 times and dried in a drying oven at 85°C to constant weight to obtain a flame retardant.
[0040] Further, the preparation process of the modified hollow glass microspheres is as follows: An appropriate amount of γ-glycidyloxypropyltrimethoxysilane was placed in anhydrous ethanol at a mass ratio of 0.17:1 and mixed thoroughly, and then the pH value was adjusted to 4.7 with hydrochloric acid to obtain a composite solution; An appropriate amount of hollow glass microspheres was placed in the composite solution at a dosage ratio of 0.28 g / mL, treated at 35 r / min for 160 min, filtered, and then placed in a drying oven at 45° C. to dry to constant weight to obtain modified hollow glass microspheres.
[0041] In this embodiment, it should be noted that the hollow glass microspheres were purchased from Shanghai Kaishengli Chemical Co., Ltd.
[0042] Among them, antioxidant 1076 is selected as the antioxidant.
[0043] In addition, this embodiment also provides a preparation process of the above-mentioned low temperature resistant, antifreeze and heat-insulating rubber and plastic, comprising the following steps: Step 1: Accurately weigh methyl vinyl silicone rubber, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tetramethyldivinyldisiloxane, hexahydrated chloroplatinic acid, silicon-containing polyurethane and antioxidant, and put the raw materials into a mixing equipment for mixing and stirring, and then perform internal mixing, extrusion and granulation to obtain granules.
[0044] Step 2: Move the pellets to a flat vulcanizer for pressure molding, and the final product is a low-temperature resistant, antifreeze and thermal insulation rubber and plastic product.
[0045] The pressure of the press molding was 7 MPa, the temperature was 1560°C, and the vulcanization time was set to 50 min.
[0046] Example 3: The preparation process of the low temperature resistant, antifreeze and heat-insulating rubber and plastic provided in the example is basically the same as that in Example 1, except that: the specific raw material composition and specific preparation process of the low temperature resistant, antifreeze and heat-insulating rubber and plastic in this example are different; the specific raw material composition and specific preparation process of the low temperature resistant, antifreeze and heat-insulating rubber and plastic in this example are as follows: A low-temperature resistant, antifreeze and heat-insulating rubber-plastic is composed of the following raw materials in parts by weight: 30 parts of methyl vinyl silicone rubber, 20 parts of polyether polyurethane, 5 parts of composite fillers, 4 parts of flame retardants, 7 parts of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, 10 parts of tetramethyl divinyl disiloxane, 6 parts of hexahydrated chloroplatinic acid, 3 parts of silicon-containing polyurethane and 5 parts of antioxidants.
[0047] In this embodiment, it should be noted that the methyl vinyl silicone rubber was purchased from Guangzhou Shisheng Chemical Co., Ltd., the polyether polyurethane was purchased from Shanghai Fengguang Plastic Technology Co., Ltd., and the silicon-based polyurethane TPU was purchased from Meirui New Materials Company.
[0048] The preparation process of the composite filler is as follows: The microporous calcium silicate is heated to 80° C., then placed in a stirring device, and γ-aminopropyltriethoxysilane is added into the stirring device, mixed for 15 minutes at 80° C. and 140 r / min, and after being discharged, placed in a drying oven at 90° C. and dried to constant weight to obtain modified microporous calcium silicate; The obtained modified microporous calcium silicate was ultrasonically differentiated for 220 minutes to obtain modified microporous calcium silicate powder, and an appropriate amount of the modified microporous calcium silicate powder was placed in deionized water at a dosage ratio of 0.12 g / mL. After ultrasonic dispersion for 30 minutes, 12% of the modified carbon fiber by weight of the modified microporous calcium silicate powder was added thereto, and the mixture was treated at 70° C. for 160 minutes. After suction filtration, the mixture was placed in a drying oven at 90° C. and dried to constant weight to obtain a composite material; An appropriate amount of the composite material was placed in deionized water at a dosage ratio of 0.22-0.32 g / mL. After ultrasonic dispersion for 30 minutes, 2.4% of methyl methacrylate and 0.22% of potassium persulfate by weight of the composite material were added thereto respectively. The mixture was refluxed for 200 minutes in a water bath at 220 r / min and 80° C. After filtration, the mixture was washed with deionized water for 5 times and dried in a drying oven at 90° C. to constant weight to obtain a thermal insulation filler.
[0049] Furthermore, the added amount of γ-aminopropyltriethoxysilane is 8.2% of the mass of the microporous calcium silicate.
[0050] The preparation process of modified carbon fiber is as follows: An appropriate amount of carbon fiber was placed in the modifier at a dosage ratio of 0.14 g / mL, and ultrasonic treatment was performed for 70 min. After the ultrasonic treatment, the temperature was raised to 70°C and refluxed at 100 r / min for 120 min. The filter cake was then filtered and washed four times with deionized water, and then placed in a drying oven at 70° C. and dried to a constant temperature to obtain modified carbon fibers.
[0051] Among them, the modifier is concentrated nitric acid with a concentration of 80%.
[0052] In this embodiment, it should be noted that microporous calcium silicate was purchased from Qinghe County Ruijiang Metal Materials Co., Ltd., and carbon fiber was purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.
[0053] In addition, the preparation process of the flame retardant is as follows: An appropriate amount of magnesium hydroxide was placed in deionized water at a dosage ratio of 0.12 g / mL and ultrasonically dispersed for 30 min to obtain a suspension; To the obtained suspension, 0.23% of magnesium hydroxide by mass of modified hollow glass microspheres was added, and the suspension was treated at 78°C and 240r / min for 320min. After filtration, the suspension was washed with deionized water for 4 times and dried in a drying oven at 90°C to constant weight to obtain a flame retardant.
[0054] Further, the preparation process of the modified hollow glass microspheres is as follows: An appropriate amount of γ-glycidyloxypropyltrimethoxysilane was placed in anhydrous ethanol at a mass ratio of 0.22:1 and mixed thoroughly, and then the pH value was adjusted to 5.2 with hydrochloric acid to obtain a composite solution; An appropriate amount of hollow glass microspheres was placed in the composite solution at a dosage ratio of 0.33 g / mL, treated at 40 r / min for 170 min, filtered, and then placed in a drying oven at 50° C. to dry to constant weight to obtain modified hollow glass microspheres.
[0055] In this embodiment, it should be noted that the hollow glass microspheres were purchased from Shanghai Kaishengli Chemical Co., Ltd.
[0056] Among them, the antioxidant is antioxidant CA.
[0057] In addition, this embodiment also provides a preparation process of the above-mentioned low temperature resistant, antifreeze and heat-insulating rubber and plastic, comprising the following steps: Step 1: Accurately weigh methyl vinyl silicone rubber, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tetramethyldivinyldisiloxane, hexahydrated chloroplatinic acid, silicon-containing polyurethane and antioxidant, and put the raw materials into a mixing equipment for mixing and stirring, and then perform internal mixing, extrusion and granulation to obtain granules.
[0058] Step 2: Move the pellets to a flat vulcanizer for pressure molding, and the final product is a low-temperature resistant, antifreeze and thermal insulation rubber and plastic product.
[0059] The pressure of the press molding was 8 MPa, the temperature was 165°C, and the vulcanization time was set to 60 min.
[0060] Comparative Example 1: The difference from Example 1 is that this example does not contain composite filler.
[0061] Comparative Example 2: The difference from Example 1 is that an equal amount of magnesium hydroxide is used to replace the flame retardant in this example.
[0062] Performance test: The low temperature resistant, antifreeze and heat preservation rubber and plastic samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the low temperature resistant, antifreeze and heat preservation rubber and plastic provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows: 1. Tear strength test: The test standard is GB / T 529-1999.
[0063] 2. Tensile strength and elongation at break test: The test standard is GB / T 528-1998.
[0064] 3. Low temperature resistance test: The test standard is GB / T 7759.2-2014 (-40×72h).
[0065] 4. Thermal insulation performance test: The testing standard is GB / T3399-1982.
[0066] 5. Flame retardant performance test: The testing standard is GB / T2406-1993.
[0067] The obtained test data are recorded in Tables 1 to 4 below.
[0068]
[0069]
[0070]
[0071]
[0072] By comparing and analyzing the relevant data in Tables 1 to 4, it can be seen that the low-temperature resistant, antifreeze and heat-insulating rubber and plastic prepared by the present invention not only has good mechanical properties, but also has excellent flame retardant properties, and at the same time, it also has excellent low-temperature resistant, antifreeze and heat-insulating properties, effectively ensuring its quality and quality. This shows that the low-temperature resistant, antifreeze and heat-insulating rubber and plastic and the preparation process thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0073] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0074] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Low temperature resistant, antifreeze and heat preservation rubber and plastic, characterized by: The invention is composed of the following raw materials in parts by weight: 20 to 30 parts of methyl vinyl silicone rubber, 6 to 12 parts of phenolic resin, 2 to 3 parts of diisopropylbenzene peroxide, 10 to 20 parts of polyether polyurethane, 3 to 5 parts of composite fillers, 2 to 4 parts of flame retardants, 4 to 7 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 6 to 10 parts of tetramethyl divinyl disiloxane, 4 to 6 parts of hexahydrated chloroplatinic acid, 2 to 3 parts of silicon-containing polyurethane and 2 to 5 parts of antioxidants; The preparation process of the composite filler is as follows: The microporous calcium silicate is heated to 70-80° C., then placed in a stirring device, and γ-aminopropyltriethoxysilane is added into the stirring device, mixed for 10-15 minutes at 70-80° C. and 120-140 r / min, and after being discharged, placed in a drying oven at 80-90° C. and dried to constant weight to obtain modified microporous calcium silicate; The obtained modified microporous calcium silicate was ultrasonically differentiated for 200 to 220 minutes to obtain modified microporous calcium silicate powder, and an appropriate amount of the modified microporous calcium silicate powder was placed in deionized water at a dosage ratio of 0.02 to 0.12 g / mL, and after ultrasonic dispersion for 20 to 30 minutes, 2% to 12% of the modified carbon fiber by weight of the modified microporous calcium silicate powder was added thereto, and the mixture was treated at 60 to 70° C. for 120 to 160 minutes, and after suction filtration, the mixture was placed in a drying oven at 80 to 90° C. and dried to constant weight to obtain a composite material; An appropriate amount of the composite material is placed in deionized water at a dosage ratio of 0.22-0.32 g / mL, and after ultrasonic dispersion for 20-30 minutes, 2.2%-2.4% of methyl methacrylate and 0.11%-0.22% of potassium persulfate by weight of the composite material are added thereto respectively, and reflux treatment is carried out for 180-200 minutes under water bath conditions of 120-220 r / min and 75-80° C., and after suction filtration, the mixture is washed with deionized water for 2-5 times, and then dried in a drying oven at 80-90° C. to constant weight to obtain a thermal insulation filler.
2. The low temperature resistant, antifreeze and heat-insulating rubber and plastic according to claim 1, characterized in that: The added amount of the γ-aminopropyltriethoxysilane is 6.2% to 8.2% of the mass of the microporous calcium silicate.
3. The low temperature resistant, antifreeze and heat-insulating rubber and plastic according to claim 1, characterized in that: The preparation process of the modified carbon fiber is as follows: Place an appropriate amount of carbon fiber in the modifier at a dosage ratio of 0.04-0.14 g / mL, and perform ultrasonic treatment for 60-70 min. After the ultrasonic treatment, heat the mixture to 50-70°C, and perform reflux treatment for 100-120 min at 80-100 r / min. The filter cake is then filtered and washed 2 to 4 times with deionized water, and then placed in a drying oven at 50 to 70° C. and dried to a constant temperature to obtain modified carbon fibers.
4. The low temperature resistant, antifreeze and heat-insulating rubber and plastic according to claim 3, characterized in that: The modifier is selected from any one of 65% to 70% concentrated sulfuric acid and 68% to 80% concentrated nitric acid.
5. The low temperature resistant, antifreeze and heat-insulating rubber and plastic according to claim 1, characterized in that: The preparation process of the flame retardant is as follows: Place an appropriate amount of magnesium hydroxide in deionized water at a dosage ratio of 0.08 to 0.12 g / mL and ultrasonically disperse for 20 to 30 minutes to obtain a suspension; Add 0.12% to 0.23% by mass of magnesium hydroxide modified hollow glass microspheres to the obtained suspension, treat at 70 to 78°C and 120 to 240 r / min for 300 to 320 min, filter, wash with deionizer 2 to 4 times, and then dry in a drying oven at 80 to 90°C to constant weight to obtain a flame retardant.
6. The low temperature resistant, antifreeze and heat-insulating rubber and plastic according to claim 5, characterized in that: The preparation process of the modified hollow glass microspheres is as follows: A suitable amount of γ-glycidyloxypropyltrimethoxysilane is placed in anhydrous ethanol at a mass ratio of 0.12 to 0.22:1 and mixed thoroughly, and then the pH value is adjusted to 4.2 to 5.2 with hydrochloric acid to obtain a composite solution; An appropriate amount of hollow glass microspheres is placed in the composite solution at a dosage ratio of 0.23 to 0.33 g / mL, treated at 30 to 40 r / min for 150 to 170 minutes, filtered, and then placed in a drying oven at 40 to 50° C. to dry to constant weight to obtain modified hollow glass microspheres.
7. The low temperature resistant, antifreeze and heat-insulating rubber and plastic according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
8. The process for preparing the low temperature resistant, antifreeze and heat insulating rubber and plastic according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, accurately weighing methyl vinyl silicone rubber, phenolic resin, diisopropylbenzene peroxide, polyether polyurethane, composite filler, flame retardant, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tetramethyl divinyldisiloxane, hexahydrated chloroplatinic acid, silicon-containing polyurethane and antioxidant, and putting the raw materials into a mixing device for mixing and stirring, and then mixing and extruding to obtain pellets; Step 2: Move the pellets to a flat vulcanizer for pressure molding, and the final product is a low-temperature resistant, antifreeze and thermal insulation rubber and plastic product.
9. The preparation process of low temperature resistant, antifreeze and heat-insulating rubber and plastic according to claim 8, characterized in that: In the step 2, the pressure of the pressurization is 6-8 MPa, the temperature is 155-165° C., and the vulcanization time is set to 40-60 min.
Citation Information
Patent Citations
Low-temperature-resistant rubber and plastic heat insulation material prepared from natural rubber
CN116622134A
Environment-friendly rubber composition and self-lubricating rubber sealing element prepared from same
CN105778509A
Transparent low-temperature-resistant scuffing-resistant polycarbonate composite material
CN106589880A
Silica gel sculpture and preparation process thereof
CN110643171A
High-temperature vulcanized silicone rubber with both electrical conductivity and ceramization potential, and preparation method thereof
CN112111159A